Incorporating Diagnostic Aspects to Mathematical Affects Inventory Development - Sun Hee Kim; Soojin Kim (International Journal of Evaluation and Research in Education (IJERE), 2013)
Many measures have been developed for the affective domain in mathematics, such as the Fennema-Sherman Mathematics Attitudes Scales (1976), Program for International Student Assessment (PISA 2003), and Trends in International Mathematics and Science Study (TIMSS 2007). However, it is difficult to find an inventory of affective attributes in mathematics that includes all affective factors based on recent theories. And affective attributes cannot be strictly differentiated, so one item can measure several factors. Thus, cognitive diagnosis theory was applied to this study, in which each item of assessment test can be allocated several attributes. The purpose of this study is to develop a Mathematical Affects Inventory (MAI) that measures student’s specific affective attributes and to verify MAI using Cognitive Diagnosis Theory. Research results will report some statistical information with affective profile of Korean students i.e. the mathematical affects of individual studentsDOI: http://dx.doi.org/10.11591/ijere.v2i4.2887